RESEARCH ON THE INFLUENCE OF TECHNOLOGICAL FORMING PARAMETERS ON THE TRIBOLOGICAL PROPERTIES OF A COMPOSITE BASED ON ULTRA-HIGH-MOLECULAR-WEIGHT POLYETHYLENE - Tomina, Anna-Mariia; Mykyta, Kateryna; Yeriomina, Yekaterina; Naberezhnaya, Olga; Frolov, Danylo (Problems of Friction and Wear, 2026)
The article presents the results of a study on the influence of technological parameters of moulding on the abrasive wear index of a polymer composite based on ultra-high-molecular-weight polyethylene containing 25 wt.% dispersed binary alloy of the Al–10 wt.%Co system as a filler. We applied the method of a full factorial experiment of type 2³ to reduce the volume of experimental tests and establish quantitative relationships between technological parameters of moulding and tribological properties of the material. We obtained an adequate mathematical model that reflects the influence of processing temperature, holding time under load, and load magnitude on the abrasive wear index. We established optimal pressing conditions which allow the wear resistance of the composite to reach its maximum value.